Sistem Pendukung Keputusan dalam Pemilihan Hotel Terbaik di Kota Medan dengan menggunakan Metode ORESTE - Agrinda Aulia Lubis (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
A hotel is one of the places needed as lodging facilities. The selection of a hotel is indispensable to the goals and needs of the visitor. In addition, a strategic location and a comfortable atmosphere are also considerations. The lack of information about hotels is one of the problems for visitors when it comes to a city to determine the desired hotel. This study develops a Decision Support System (SPK) to choose the best hotel in Medan City using the Outranking RElation Sorting method on basis of Threshold Exploration (ORESTE). This system is designed to assist visitors in choosing a hotel that meets the desired criteria. The Outranking RElation Sorting method on basis of Threshold Exploration (ORESTE) is used to determine the weight of each attribute and perform alternative ranking of hotels. In this study, the criteria used include the type of hotel, location, facilities, service and price. This system is expected to help visitors in making more precise and objective decisions. The results of the study show that this SPK system can help visitors in choosing the best hotel that suits their needs.